2016
DOI: 10.3389/fpsyt.2015.00188
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind in Bipolar Disorder, with Comparison to the Impairments Observed in Schizophrenia

Abstract: Our ability to make sense of information on the potential intentions and dispositions of others is of paramount importance for understanding their communicative intent, and for judging what an appropriate reaction might be. Thus, anything that impinges on this ability has the potential to cause significant social impairment, and compromise an individual’s level of functioning. Both bipolar disorder and schizophrenia are known to feature theory of mind impairment. We conducted a theoretical review to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 138 publications
1
27
1
Order By: Relevance
“…Moreover, in our study we also found that BD patients had FDG uptake alterations in middle and inferior temporal cortex, regions found to be widely involved in the pathogenesis of mood disorders . This is not surprising especially because the temporal lobe is associated with several cognitive functions, such as language processing and Theory of Mind, that are often described impaired in BD patients . Moreover, the temporal cortex is functionally connected to the amygdala and prefrontal cortex and it seems to have a role in detection and representation of emotions, along with occipital cortex .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, in our study we also found that BD patients had FDG uptake alterations in middle and inferior temporal cortex, regions found to be widely involved in the pathogenesis of mood disorders . This is not surprising especially because the temporal lobe is associated with several cognitive functions, such as language processing and Theory of Mind, that are often described impaired in BD patients . Moreover, the temporal cortex is functionally connected to the amygdala and prefrontal cortex and it seems to have a role in detection and representation of emotions, along with occipital cortex .…”
Section: Discussionsupporting
confidence: 76%
“…28 This is not surprising especially because the temporal lobe is associated with several cognitive functions, such as language processing and Theory of Mind, 29 that are often described impaired in BD patients. 30 Moreover, the temporal cortex is functionally connected to the amygdala and prefrontal cortex and it seems to have a role in detection and representation of emotions, along with occipital cortex. 17 Our results seem therefore in line with previous studies, showing a GM shrinkage 28 and an altered metabolic function 16,31 in temporal areas in BD patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still some other studies which found significant relationships between ToM impairment with clinical symptoms and general cognitive functions (Bora et al, 2016a;Bora et al, 2009b). Mitchell and Young (2015) think that the relationship between ToM impairments with positive psychotic symptoms may not be disease-specific, but symptom-specific. Marjoram et al (2005) examined ToM abilities in patients with SCZ and affective disorders and found that hallucinations and delusions were associated with ToM impairment, regardless of diagnosis.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, a meta-analysis identified significant impairments in tasks involving theory of mind in individuals with schizophrenia 16 . Difficulties in theory of mind have also been identified in people with unipolar and bipolar disorders [17][18][19] , eating disorders 20 , and attention deficit and hyperactivity disorder or ADHD 21 . For example, a recent meta-analysis of theory of mind in people with eating disorders (15 studies, 677 cases and 514 controls) identified significant deficits in theory of mind in individuals with anorexia compared to typical controls 22 .…”
Section: Introductionmentioning
confidence: 99%